Necessary defense as a circumstance precluding criminality: national and international aspects - Рощина, Інна Олександрівна; Гудзь, Сергій Дмитрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article defines the concept of self-defense under the criminal legislation of Ukraine and the criminallaws of the countries of continental Europe, identifies key features and characteristics of self-defense shall beconsidered conditions of validity of self-defense.